Effect of two levels of AD3EC on the rumen environment of local lambs. - shteeb, huda (University of Thi-Qar Journal of agricultural research, 2025)
This study aimed to investigate the effect of two levels of AD3EC on the rumen environment of local lambs during the period, from,2\1\2025 to 1\4\2025. The study was conducted at the Agricultural Station affiliated with the College of Agriculture and Marshes. Twelve local sheep lambs at weaning age were purchased and divided into three treatments, with four lambs per treatment, having an average weight of 13.00–13.55 kg. The first treatment served as the control and was not administeredAD3EC,left for comparison. The second treatment received3 ml of AD3EC, and the third treatment received4 ml of AD3EC. All lambs were fed the same diet. The results showed that in the first, second, and third months of the study, there was a significant increase in pH values for the treatments receivingAD3EC compared to the control treatment. Additionally ,regarding total bacteria, in the first, second, and third months, there was a significant increase in total bacterial counts for the treatments that receivedAD3EC,compared to the control treatment